Índice de desenvolvimento dos estados brasileiros: teoria do desenvolvimento humano, proposição metodológica e cálculo - Cardoso, Richard da Silva Alves (2014)
This dissertation deals with human development based on studies of Amartya Sen who has the people and enhancement of the welfare of society as the center of concerns. The objective is to estimate an index of development for the Brazilian states and the Federal District into two distinct periods. The first period comprises the following years the Real Plan based on 1996 and the second period, the most recent years, refers to 2010. State Development Index (SDI) is calculated by means of multivariate statistical analysis technique called Factor Analysis. Twenty one (21) variables of aspect economic, demographic, social, security, infrastructure and agriculture are used. The variables were divided into four (4) groups (demographic and economic, infrastructure and support, social and agricultural), allowing to calculate partial indexes and formulate specific policies for punctual improvements. The comparison between the periods in question and check the trajectory of human development of the Brazilian states through SDI suggests that most states obtained reductions in the level of human development. The Federal District and the states of Mato Grosso, Tocantins, Roraima, Amapá and Acre were the exceptions, and failed to improve human development. Another comparison is made between the IDE and the Human Development Index (HDI) to check for similarities and differences. The main similarity refers to the classification of states regarding development.